Assessment of attributes for family and community guidance in the child health - Juliane Pagliari Araujo; Cláudia Silveira Viera; Beatriz Rosana Gonçalves de Oliveira Toso; Neusa Collet; Patrícia Oehlmeyer Nassar (Escola Paulista de Enfermagem, Universidade Federal de São Paulo, 2014)
Objective To identify the extension in primary health services of attributes for family and community guidance about the health of children health. Methods This was a quantitative, cross-sectional and evaluation study. We administered 548 questionnaires (Brazilian Primary Care Assessment Tool, child version) to families and/or legal guardians of children younger than 12 years of age who were received care in 24 health units. Data were analyzed using SPSS software, version 17.0. Results The basic public health services of the studied municipality were below what is considered ideal for primary health care with regard to the attributes of family and community guidance. Score of these attributes were 4.4 and 5.1, respectively. Scores considered satisfactory were ≥6.6. Conclusion We found that it was difficult for services to integrate families and the community in the care process. This finding reinforces the healing care culture and individual-centered care.